PEMAHAMAN KONSEP KESELAMATANGURU PENDIDIKAN JASMANI SEKOLAH DASAR - Yustinus Sukarmin (Jurnal Pendidikan Jasmani Indonesia, 2011)
AbstractThe research focuses on accidents, which typically occur during the teaching process of sports at elementary schools that result from teachers’ lack of understanding on the concept of safety. Therefore, the researcher conducted this research to find out the safety concept understanding of elementary school physical educators. This research is a descriptive research that used of only one variable; safety concept understanding. The populations involved in the research were elementary school physical educators from Bantul regency. The researcher randomly selected 175 out of 304 teachers as samples using proportional sampling technique. The instrument used for the research was a questionnaire consisting of 40 items designed by the researcher. The data were analyzed using descriptive-quantitative technique with percentage. The finding of the research shows that the safety concept understanding on the elementary school physical educators were generally good (81,19 %), good from the human aspect (82,22 %), average from the environment aspect (80,14 %), average from the student aspect (70,86 %), good from the teacher aspect (93,60 %), good from the physical aspect (85,34 %), and average from the weather aspect (73,94 %). The result indicates that the teachers were highly aware of their students’ safety during the sport teaching lessons.Keywords: understanding, safetyAbstrakPenelitian ini membahas tentang kecelakaan dalam proses pembelajaran penjas di SD yang salah satu faktor penyebabnya adalah kurangnya pemahaman konsep keselamatan para guru penjas. Oleh sebab itu, penelitian ini dilakukan dengan tujuan untuk mengetahui pemahaman konsep keselamatan guru penjas SD. Penelitian ini merupakan penelitian deskriptif dengan menggunakan satu variabel, yaitu: pemahaman konsep keselamatan. Populasi yang digunakan dalam penelitian ini adalah guru penjas SD se-Kabupaten Bantul. Peneliti menggunakan 175 orang dari 304 orang sebagai sampel yang diambil secara random dengan teknik sampel proporsi atau proportional sampling. Instrumen penelitian menggunakan angket tertutup buatan sendiri yang terdiri atas 40 butir. Teknik analisis data menggunakan teknik deskriptif kuantitatif dengan persentase. Hasil penelitian menunjukkan bahwa pemahaman konsep keselamatan guru penjas SD secara umum baik (81,19 %); dari aspek manusia baik (82,22 %); dari aspek lingkungan cukup (80,14 %); dari aspek murid cukup (70,86 %); dari aspek guru baik (93,60 %); dari aspek fisik baik (86,34 %); dan dari aspek cuaca cukup (73,94 %). Hasil ini mengandung makna bahwa guru penjas SD memiliki kepedulian yang cukup tinggi terhadap keselamatan para siswa pada waktu mengikuti pelajaran penjas.Kata Kunci: pemahaman, keselamatan